Alterations in Inflammatory Cytokines and Redox Homeostasis in LPS-Induced Pancreatic Beta-Cell Toxicity and Mitochondrial Stress: Protection by Azadirachtin - John, Annie; Raza, Haider (Frontiers in Cell and Developmental Biology, 2022)
Inflammation and redox imbalance are hallmarks of cancer, diabetes, and other degenerative disorders. Pathophysiological response to these disorders leads to oxidative stress and mitochondrial dysfunction by alterations and reprogramming in cellular signaling and metabolism. Pancreatic beta cells are very sensitive to the inflammatory and altered nutrient signals and hence play a crucial role in diabetes and cancer. In this study, we treated insulin-secreting pancreatic beta cells, Rin-5F, with the bacterial endotoxin, LPS (1 μg/ml) to induce an inflammatory response in vitro and then treated the cells with a known anti-inflammatory, anticancer and antioxidant phytochemical, azadirachtin (AZD, 25 µM for 24 h). Our results demonstrated lipid peroxidation and nitric oxide production causing increased nitro/oxidative stress and alterations in the activities of anti-oxidant enzymes, superoxide dismutase and catalase after LPS treatment. Pro-inflammatory responses caused by translocation of nuclear factor kappa B and release of inflammatory cytokines were also observed. These changes were accompanied by GSH-dependent redox imbalance and alterations in mitochondrial membrane potential and respiratory complexes enzyme activities leading to mitochondrial respiratory dysfunction, reduced ATP synthesis, and intrinsic caspase-9 mediated apoptosis. Caspase-9 was activated due to alterations in Bcl-2 and Bax proteins and release of cytochrome c into the cytosol. The activities of oxidative stress-sensitive mitochondrial matrix enzymes, aconitase, and glutamate dehydrogenase were also inhibited. Treatment with AZD showed beneficial effects on the recovery of antioxidant enzymes, inflammatory responses, and mitochondrial functions. GSH-dependent redox homeostasis also recovered after the treatment with AZD. This study may help in better understanding the etiology and pathogenesis of inflammation-induced disorders in pancreatic beta cells to better manage therapeutic strategies.